Kinetic Study of the Acylation Reaction of Dibutylcarbamyl Chloride and Dibutylamine - Zhou, Yi-Bo; Zhu, Rui; Zhou, Han-Qi; Li, Jun-Hua; Liu, Feng-Fan (Pharmaceutical Fronts, 2023)
Tetrabutylurea (TBU) is mainly used as a working liquid in the preparation of hydrogen peroxide via the anthraquinone process. It is reported that dibutylamine (A) reacts with dibutylcarbamyl chloride (B) to produce TBU in the presence of triphosgene, which is the decisive step of the reaction. In this study, we aimed to investigate the reaction kinetics of the decisive step to gain more insight into the reaction. The reaction order as well as the pre-exponential factors (A) and the activation energies (Ea) were determined. The kinetic study suggested that the total order of the reaction is second. Ea = 5.4 × 104 J/mol, A = 1.5257 × 107 L/(mol × min), calculated through a second-order kinetics model. The accuracy and applicability of the kinetic model were verified by serval experiments, showing that enhancing reaction temperature could shorten the reaction time and increase the conversion rate.
Keywords: tetrabutylurea; dibutylamine; dibutylcarbamyl chloride; kinetics; acylation